Immunogenicity and safety of a pentavalent meningococcal ABCWY vaccine in adolescents and young adults: an observer-blind, active-controlled, randomised trial - Peterson, James; Drazan, Daniel; Czajka, Hanna; Maguire, Jason; Pregaldien, Jean-Louis; Seppa, IIkka; Maansson, Roger; O'Neill, Robert; Balmer, Paul; Jodar, Luis; Jansen, Kathrin U; Anderson, Annaliesa S; et al. (Lancet. Infectious diseases, 2023)
BACKGROUND: Meningococcal serogroups A, B, C, W, and Y cause nearly all meningococcal disease, and comprehensive protection requires vaccination against all five serogroups. We aimed to assess the immunogenicity and safety of a pentavalent MenABCWY vaccine comprising two licensed vaccines-meningococcal serogroup B-factor H binding protein vaccine (MenB-FHbp) and a quadrivalent meningococcal serogroup ACWY tetanus toxoid conjugate vaccine (MenACWY-TT)-compared with two doses of MenB-FHbp and a single dose of quadrivalent meningococcal serogroup ACWY CRM197-conjugate vaccine (MenACWY-CRM) as the active control. We previously reported the primary safety and immunogenicity data relating to the two-dose MenB-FHbp schedule. Here we report secondary outcomes and ad-hoc analyses relating to MenABCWY immunogenicity and safety. METHODS: We did an observer-blind, active-controlled trial at 68 sites in the USA, Czech Republic, Finland, and Poland. Healthy individuals (aged 10-25 years) who had or had not previously received a MenACWY vaccine were randomly assigned (1:2) using an interactive voice or web-based response system, stratified by previous receipt of a MenACWY vaccine, to receive 0·5 mL of MenABCWY (months 0 and 6) and placebo (month 0) or MenB-FHbp (months 0 and 6) and MenACWY-CRM (month 0) via intramuscular injection into the upper deltoid. All individuals were masked to group allocation, except staff involved in vaccine dispensation, preparation, and administration; and protocol adherence. Endpoints for serogroups A, C, W, and Y included the proportion of participants who achieved at least a four-fold increase in serum bactericidal antibody using human complement (hSBA) titres between baseline and 1 month after each vaccination. For serogroup B, secondary endpoints included the proportion of participants who achieved at least a four-fold increase in hSBA titres from baseline for each of four primary test strains and the proportion of participants who achieved titres of at least the lower limit of quantitation against all four test strains combined at 1 month after the second dose. Endpoints for serogroups A, C, W, and Y were assessed in the modified intent-to-treat (mITT) population, which included all randomly assigned participants who received at least one vaccine dose and had at least one valid and determinate MenB or serogroup A, C, W, or Y assay result before vaccination up to 1 month after the second dose, assessed in ACWY-experienced and ACWY-naive participants separately. Secondary endpoints for serogroup B were analysed in the evaluable immunogenicity population, which included all participants in the mITT population who were randomly assigned to the group of interest, received all investigational products as randomly assigned, had blood drawn for assay testing within the required time frames, had at least one valid and determinate MenB assay result after the second vaccination, and had no important protocol deviations; outcomes were assessed in both ACWY-experienced and ACWY-naive populations combined. Non-inferiority of MenABCWY to MenACWY-CRM and MenB-FHbp was determined using a -10% non-inferiority margin for these endpoints. Reactogenicity and adverse events were assessed among all participants who received at least one vaccine dose and who had available safety data. This trial is registered with Clinicaltrials.gov, NCT03135834, and is complete. FINDINGS: Between April 24 and November 10, 2017, 1610 participants (809 MenACWY-naive; 801 MenACWY-experienced) were randomly assigned: 544 to receive MenABCWY and placebo (n=272 MenACWY-naive; n=272 MenACWY-experienced) and 1066 to receive MenB-FHbp and MenACWY-CRM (n=537 MenACWY-naive; n=529 MenACWY-experienced). Among MenACWY-naive or MenACWY-experienced MenABCWY recipients, 75·5% (95% CI 69·8-80·6; 194 of 257; serogroup C) to 96·9% (94·1-98·7; 254 of 262; serogroup A) and 93·0% (88·4-96·2; 174 of 187; serogroup Y) to 97·4% (94·4-99·0; 224 of 230; serogroup W) achieved at least four-fold increases in hSBA titres against serogroups ACWY after dose 1 or 2, respectively, in ad-hoc analyses. Additionally, 75·8% (71·5-79·8; 320 of 422) to 94·7% (92·1-96·7; 396 of 418) of MenABCWY and 67·4% (64·1-70·6; 563 of 835) to 95·0% (93·3-96·4; 782 of 823) of MenB-FHbp recipients achieved at least four-fold increases in hSBA titres against MenB strains after dose 2 in secondary analyses; 79·9% (334 of 418; 75·7-83·6) and 74·3% (71·2-77·3; 605 of 814), respectively, achieved composite responses. MenABCWY was non-inferior to MenACWY-CRM (single dose) and to MenB-FHbp in ad-hoc analyses based on the proportion of participants with at least a four-fold increase in hSBA titres from baseline and (for MenB-FHbp only) composite responses. Reactogenicity events after vaccination were similarly frequent across groups, were mostly mild or moderate, and were unaffected by MenACWY experience. No adverse events causing withdrawals were related to the investigational product. Serious adverse events were reported in four (1·5%; 0·4-3·7) MenACWY-naive individuals in the MenABCWY group versus six (2·2%; 0·8-4·8) among MenACWY-experienced individuals in the MenABCWY group and 14 (1·3%; 0·7-2·2) in the active control group (MenACWY-experienced and MenACWY-naive individuals combined); none of these were considered related to the investigational product. INTERPRETATION: MenABCWY immune responses were robust and non-inferior to MenACWY-CRM and MenB-FHbp administered separately, and MenABCWY was well tolerated. The favourable benefit-risk profile supports further MenABCWY evaluation as a simplified schedule compared with current adolescent meningococcal vaccination programmes. FUNDING: Pfizer.
Keywords: vakcinace; Humans; Vaccines, Conjugate; meningokokové infekce; Neisseria meningitidis séroskupiny B; Vaccination; Neisseria meningitidis, Serogroup B; mladý dospělý; protilátky bakteriální; kombinované vakcíny; lidé; Meningococcal Infections; mladiství; Meningococcal Vaccines; Antibodies, Bacterial; Immunogenicity, Vaccine; Adolescent; Vaccines, Combined; Young Adult; imunogenicita vakcíny; vakcíny konjugované; meningokokové vakcíny; Neisseria meningitidis